Screening Retinopathy of Prematurity in Extremely Low Birth Weight Infants in China and the Need for Earlier Screening Times - Jianxun Wang; Feng Chen; Shiping He; Daoman Xiang (Journal of Ophthalmology)
Purpose. To convey the need for a revised screening strategy for retinopathy of prematurity (ROP) for extremely low birth weight (ELBW) infants in China. Design. A retrospective longitudinal study. Methods. The medical charts of infants with a birth weight (BW) of less than 1 kg were reviewed. The infants were divided into three groups: group A, without ROP; group B, with ROP but not up to type 1 prethreshold or threshold ROP; group C, with type 1 prethreshold or threshold ROP. Data collected included gender, gestational age (GA), BW, postmenstrual age (PMA), age of onset of ROP, and age at which treatment was carried out, if required. Results. A total of 77 infants were involved. Fifty-six infants developed ROP at any stage and 38 infants developed type 1 prethreshold or threshold ROP. The mean BW and GA of infants in group A were significantly different compared with groups B and C. The mean PMA of onset of ROP in infants who developed mild ROP was 37 weeks compared with 34 weeks for infants who developed severe ROP. Conclusion. ELBW infants have a higher incidence of ROP in China which highlights the need for optimizing neonatal care for these infants. In ELBW infants, ROP tends to develop more severely when it occurs earlier. It is necessary for ELBW infants, especially for those with a BW less than 800 g or a GA less than 25 weeks, to be initially screened at an earlier time.